HUBUNGAN KARAKTERISTIK DAN TEKANAN SOSIAL DENGAN PERILAKU PENCEGAHAN PENULARAN HIV/AIDS PADA WBP DI LAPAS KELAS IIA PADANG - Sri Mindayani; Hilda Hidayat (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2018)
Data on the prevalence of Biological Integrated Surveillance and Behavior of the Ministry of Health in 2011 found that the prevalence of HIV and syphilis among prisoners was 3% and 5%. Penitentiary (Lapas) Class IIA Padang is one of the Penitentiary in West Sumatra Province that has HIV / AIDS cases. There are risky behaviors that cause WBP at risk of being infected with HIV/AIDS. This study aims to determine the behavior of prevention of HIV/AIDS transmission in WBP at the Padang II Class IIA Penitentiary in 2018. This type of research is analytical with a cross sectional design. This research was conducted from January - September 2018 Penitentiary Class IIA Padang. The study population numbered 1375 people and the number of samples was 94 people. Sampling is done by simple random sampling technique. Primary data collection is done by interviewing techniques using a questionnaire. Data analysis included univariate analysis and bivariate analysis. The results of the study indicate a relationship between social pressure, and the behavior of prevention of HIV/AIDS transmission in WBP in Padang Class IIA Prison. The results of the study also showed no relationship between age, education, ethnicity. It is recommended that officers from the Penitentiary need to collaborate with relevant stakeholders, such as the Padang City Health Office, to conduct direct monitoring of WBP who are still using narcotics. There needs to be an increase in the socialization of prevention of HIV/AIDS transmission in the Penitentiary Class IIA Padang.Keywords: Characteristics, Social Pressure, Behavior, HIV/AIDS